Seleção para características reprodutivas em bovinos de corte da raça Nelore - Moreira, Heverton Luis; Buzanskas, Marcos Eli [UNESP]; Munari, Danisio Prado [UNESP]; Canova, Érika Breda; Lôbo, Raysildo Barbosa; de Paz, Claudia Cristina Paro (FapUNIFESP (SciELO), 2015)
Genetic breeding programs of beef cattle in Brazil are including new features, mainly related to reproductive efficiency. Thus, it is necessary to study the effectiveness of selection and quantify genetic gain for these traits in herds. This study estimated genetic and phenotypic parameters and genetic trends for reproductive traits used in breeding programs for Nelore beef cattle. The traits studied were the scrotal circumference (SC) at 365 and 450 days of age (SC365 and SC450), age at first calving (AFC) and gestation length, as a cow trait (GLcow) and a calf trait (GLcalf). The (co)variance components were obtained with the Restricted Maximum Likelihood Methodology in a single and double-trait analysis of the animal model. For scrotal circumference (SC365 and SC450), positive and favorable genetic gains were observed. For AFC, GLcow and GLcalf, the trends were favorable for selection, but without significant genetic gain. Selection for large SC may reduce AFC and improve female reproductive efficiency. The selection for reproductive traits (SC365, SC450, AFC and GL) may improve reproductive and productive efficiency of Nelore cattle, if used as a selection criterion.
Reproductive traits selection in nelore beef cattle
Keywords: Genetic evaluation; Precocity; Reproductive efficiency